Indonesian Muslim Youth and the Discourse on the Caliphate System, Islamic State and Sharia-Based Regional Regulations in the Post-Reform Era - Ahmad, Maghfur (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2021)
This study analyzes the discourse on the caliphate system, the Islamic state, and Sharia-based regional regulations among Indonesian Muslim youth. Following the reform era in Indonesia, the rise of Islamic studies and political discourse was accompanied by a significant resurgence of Islamic conservatism. Discussions on jihad, the caliphate, Sharia-based regional regulations, and efforts to establish an Islamic state became increasingly prominent. This research employs a qualitative approach, with data collected through interviews, observations, and documentation among millennial Islamic activists attending public schools in Pekalongan City, Central Java, Indonesia. The data were analyzed using an interactive analysis model developed by Miles and Huberman. The findings reveal that Muslim youth exhibit multiple, often conflicting perspectives. While they aspire to practice Islam comprehensively in all aspects of life, they also acknowledge that Pancasila (the Five Principles) remains the most suitable foundation for governance in Indonesia's pluralistic society, on the one hand. Moreover, the study highlights a widespread lack of literacy among Indonesian youth regarding the historical debates on the relationship between religion and the state during Indonesia’s founding. This gap affects their understanding and contextualization of the discourse on the caliphate system, Islamic state, and Sharia regulations. On the other hand, the rise of textual interpretations and minimal awareness of nationalism and civic literacy poses a potential threat to Indonesia’s future as a unified nation. This research contributes to the discourse on Islamic political thought and youth studies by examining the complex interplay between religious aspirations and national identity among Indonesian Muslim youth. It underscores the need for educational interventions to enhance understanding of the historical and contextual dimensions of religion-state relations, fostering a balanced approach to nationalism and religious values.